Antithrombotic therapy in pediatric ventricular assist devices: Multicenter survey of the European EXCOR Pediatric Investigator Group - Miera, Oliver; Schmitt, Katharina L.; Akintuerk, Hakan; Boet, Angele; Cesnjevar, Robert; Chila, Teresa; Fleck, Thilo; Goldwasser, Ranny; Guereta, Luis G.; Heineking, Beatrice; Hoerer, Juergen; Horke, Alexander; et al. (The international journal of artificial organs, 2018)
OBJECTIVES: Mechanical circulatory support for pediatric heart failure patients with the Berlin Heart EXCOR ventricular assist system is the only approved and established bridging strategy for recovery or heart transplantation. In recent years, the burden of thromboembolic events has led to modifications of the recommended antithrombotic therapy. Therefore, we aimed to assess modifications of antithrombotic practice among the European EXCOR Pediatric Investigator Group members. - METHODS: We sent a questionnaire assessing seven aspects of antithrombotic therapy to 18 European hospitals using the EXCOR device for children. Returned questionnaires were analyzed and identified antithrombotic strategies were descriptively compared to "Edmonton protocol" recommendations developed for the US EXCOR pediatric approval study. - RESULTS: Analysis of 18 received surveys revealed substantial deviations from the Edmonton protocol, including earlier start of heparin therapy at 6-12 h postoperatively and in 50% of surveyed centers, monitoring of heparin effectiveness with aPTT assay, administering vitamin K antagonists before 12 months of age. About 39% of centers use higher international normalized ratio targets, and platelet inhibition is changed in 56% including the use of clopidogrel instead of dipyridamole. Significant inter-center variability with multiple deviations from the Edmonton protocol was discovered with only one center following the Edmonton protocol completely. - CONCLUSION: Current antithrombotic practice among European EXCOR users representing the treatment of more than 600 pediatric patients has changed over time with a trend toward a more aggressive therapy. There is a need for systematic evidence-based evaluation and harmonization of developmentally adjusted antithrombotic management practices in prospective studies toward revised recommendations.
Gesehen am 16.04.2020